Strategies and Techniques for the Internationalization of Non-Dominant Firms: A Qualitative Study - Makaya, Wilson Freddy; Nwachukwu, Chijioke; Hieu, Vu Minh (International Journal of Innovative Research and Scientific Studies, 2021)
This study focuses on the strategies and techniques used by small or medium-sized enterprises (SMEs) to join and dominate large firms in global markets. The analytical works refer to the prevailing writings on international markets and entrepreneurship. Based on the categorizations and analyses of the themes and sub-themes, the historical development of global markets and theories is recounted, thereby creating a foundation for assessing the strategies and techniques of non-dominant firms. The findings indicate that the number of small and medium enterprises joining international markets is growing due to the adoption of robust strategies and techniques. An international model is proposed, which consists of three techniques of the Diaspora approach, social media approach, and re-approach, along with strategies that consist of three dimensions: a big dream or desire to internationalize, a need to internationalize, and an ability to internationalize." This paper provides a point of reference for practitioners and researchers interested in attaining comprehensive insight into internationalization.